Group A Streptococcal Toxic Shock-Like Syndrome in a Male Presenting as Primary Peritonitis: A Case Report and a Review in Japan. (24th December 2019) - Sakuraba, Shunsuke; Ueda, Shuhei; Tokuda, Satoshi; Ito, Tomoaki; Kushida, Tomoyuki; Sakurada, Mutsumi; Maekawa, Hiroshi; Sato, Koichi
Abstract : Background. Streptococcal toxic shock-like syndrome (TSLS) is a severe infection caused by group A hemolytic streptococcus. It is clinically characterized by rapidly progressive septic shock and multiple organ failure within just a few hours. TSLS presenting as primary peritonitis is rare, especially in a male. Herein, we report a case of TSLS in a male presenting with primary peritonitis, with a review of 25 cases in Japan. Case Presentation. A 51-year-old male was referred to our hospital with abdominal pain and hypotension. We made a preoperative diagnosis of peritonitis with septic shock and performed an emergency operation. Intraoperative findings indicated no marked origin of the peritonitis. Preoperative blood culture showed the presence of group A hemolytic streptococcus. The patient required intensive care involving artificial respiration, abdominal drainage and cytokine absorption therapy, and was discharged on postoperative day 25. Conclusion. TSLS in a male presenting as primary peritonitis is rare. Although this condition is a severe infection, it can be treated by multimodal therapy.